Brucella Synovitis in Ninevah Province - Al-Khalidi, rakan; Baghdasarian, Zvart (Iraqi National Journal of Nursing Specialties, 2005)
Abstract Out of 222 patients complaining from signs and symtomps raised suspicion for brucellosis, 39 (16 males and 23 females) further more they suffered from joint and/or swelling. Blood and synovial fluid (SF) from each patient were subjected to serological tests and culture. Concerning SF specimens the investigations were extended to gross examination, Blood-Synovial Fluid Glucose Difference (G-S.F.G.D), protein determination, total and differential W.B.C. count. The investigations revealed high agglutinin titres in both blood and SF specimens, abnormal gross appearance, high value (beyond normal) of B-S.F.G.D., protein, total and differential W.B.C. count. The authors succeeded in isolating brucellae 34 and 36 of blood and SF specimens respectively, with predominance of Brucella abortus (26 out of 36). Therefore this study recommends on looking after synovitis due to brucella whenever symptoms rais the suspicion of brucellosis or even when a patient complain from joint pain and also on doing culture for exclusive diagnosis and specific medication. Eventually to have an epidemiological concept, and determining resistance emergency of the isolates.